Memaksimalakan Fotografi Smartphone dan Smart Bermedia Social Dalam Meningkatkan Kegitan UMKM Desa Kiringan Boyolali - Putro, Fanny Hendro Aryo; Setiawan, Topan (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
The development of technology and information is progressing rapidly and driving transformation in the way people communicate. Humans are required to continuously adapt to technological advances, including in community service activities that carry the theme of digital media. This community service activity took the form of socialization and training in various fields of communication, particularly the application of new media. The target of this activity was Kiringan Village, Boyolali Regency, with a focus on the PKK group of women who are active in MSME activities. Social media has become part of people's daily routines, but its use to support the development of village MSMEs is still not optimal. This phenomenon is the background for the implementation of community service activities aimed at transferring knowledge and skills in the productive use of communication media. The community service uses an audience ethnography approach, considering the relatively traditional character of the Kiringan Village community. Through this socialization, the community is expected to be better prepared to face the positive and negative impacts of digital media in the development of village MSMEs.